The Microeconomics of Sudden Stop Episodes – An Application to the Euro Area - Bernhofer, Dominik (Momentum Quarterly, 2014)
This study examines the foreign claims of BIS-reporting transnational banks on the euro area economies since the bankruptcy of Lehman Brothers and tries to understand the decline in foreign claims by employing a simple model of multiple equilibria. The underlying reasoning suggests that it was rational for banks to push the euro area periphery to the brink of bankruptcy and that bold economic policy measures effectively stabilized the associated adverse economic consequences. In the model presented here, solidarity among the euro area countries emerges as the most important precondition for integrated financial markets, as it prevents coordination failures among transnational banks and thereby guarantees financial stability.
Keywords: euro area crisis; transnational banks; coordination failure; financial integration